Judge Al Villa Swears In New Attorney Cristobal Perez - Watkins, Howard::::::::: (1983)
Judge Al Villa, Catalina Peralta, Ruben Lucero, Cristobal Perez, Aggie Rose, Betsy Temple, Charles Kahill in courtroom